Analysis of the Formation of Sauce-Flavored Daqu Using Non-targeted Metabolomics - Luo, Shuai; Zhang, Qiaoling; Yang, Fan; Lu, Jianjun; Peng, Zheng; Pu, Xiuxin; Zhang, Juan; Wang, Li (Frontiers in Microbiology, 2022)
Sauce-flavored Daqu exhibits different colors after being stacked and fermented at high temperatures. Heiqu (black Daqu, BQ) with outstanding functions is difficult to obtain because its formation mechanism is unclear. In this study, we compared the metabolites in different types of Daqu using ultra-high-performance liquid chromatography triple quadrupole mass spectrometry to explore the formation process of BQ. We found that 251 differential metabolites were upregulated in BQ. Metabolic pathway analysis showed that "tyrosine metabolism" was enriched, and most metabolites in this pathway were differential metabolites upregulated in BQ. The tyrosine metabolic pathway is related to enzymatic browning and melanin production. In addition, the high-temperature and high-humidity fermentation environment of sauce-flavored Daqu promoted an increase in the melanoidin content via a typical Maillard reaction; thus, the melanoidin content in BQ was much higher than that in Huangqu and Baiqu. By strengthening the Maillard reaction precursor substances, amino acids, and reducing sugars, the content of Daqu melanoidin increased significantly after simulated fermentation. Therefore, the enzymatic browning product melanin and Maillard reaction products melanoidins are responsible for BQ formation. This study revealed the difference between BQ and other types of Daqu and provides theoretical guidance for controlling the formation of BQ and improving the quality of liquor.